RANCANG BANGUN OPERASIONAL TEKNOLOGI INFORMASI BANK SENTRAL MELALUI SISTEM SDM OUTSOURCING - Tjiptogoro Dinarjo; Eriyatno Eriyatno; Aji Hermawan; M. Joko Affandi (School of Business, Bogor Agricultural University (SB-IPB), 2011)
The key factors of successful information technology outsourcing are the procurement process of the professional and trusted provider, the contract that guarantees a committed implementation of outsourcing as agreed priorly, the implementation of outsourcing that fulfils the approved grade of quality as service level agreement, the provider’s capabilities as listed in the requirement of the procurement process, and the implementation itself. Those key factors are the subjects of study, which results are applicable as the basic policy in developing a premium IT services through the outsourcing system. The case study was conducted in the Bank Indonesia, whether research approach is the combination of explorative, descriptive and explanator. Analysis endogenous and exogenous variables’ll be using Structural Equation Modeling (SEM). The recommendation is formulated according to the result of SEM analysis. Result of the study stated that Structural Model 3 is the perfect fit model. The dominant factor is the capability, procurement, contracts, implementation and outsourcing of IT operations significantly on the structure of 3. Keywords: Outsourcing, Information Technology, Structural Model, Manajemen Sumber Daya Manusia